Image Steganography combined with Cryptography - Paruchuri, Vijaya Lakshmi; Sridevi, Dr.R.; Rao, K.S. SadaSiva (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Steganography is the science of invisible communication. Apart from the sender and intended recipient no one suspects the existence of the message. Using Steganography, information can be hidden in various mediums known as carriers. The carriers can be images, audio files, video files and text files. Image Steganography is a technique of using an image file as a carrier. Cryptography protects the information by applying the encryption and decryption techniques, so that the secret message can be understood only by the right person. This paper proposes a method, which combines the techniques of Steganography and cryptography, to hide the secret data in an image. In the first phase, the sender will embed the secret data in an image by using the Least Significant Bit (LSB) technique. The embedded image will be encrypted by using an encryption algorithm. At final, the encrypted image will be decrypted and the hidden data will be retrieved by supplying the valid secret key by the receiver. The process includes the phases of Data embedding, Image Encryption and recovery of both original image and secret data from the encrypted image.